ANALYSIS OF CAUSATIVE FACTORS FOR CANKER DISEASE EPIDEMIC ON RUBBER PLANTS IN SOUTH SUMATRA - Febbiyanti, Tri Rapani; Wiyono, Suryo; Yahya, Sudirman; Widodo, Widodo (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2019)
Analysis of Causative Factors for Canker Disease Epidemic on Rubber Plants in South Sumatra.  Lasiodiplodia theobromae is the cause of stem canker in the rubber plant (Hevea brasiliensis), this is a new disease and has never been reported in Indonesia. Currently, data on environmental factors and cultivation techniques related to the development of stem canker are not available so research needs to be done on this subject. The objective of the study was to analyze environmental factors and cultivation techniques related to stem canker on rubber trees in southern Sumatra. The study was conducted by collecting data on environmental factors and cultivation techniques and then analyzed the association with stem canker. Field observation was carried out at 21 locations in PT. Perkebunan Nusantara VII Business Unit Padang Plawi Bengkulu,  Tulung Buyut Lampung, Musilandas Palembang and Experimental Garden of Sembawa Research Center, Indonesian Rubber Research Institute at Palembang to measure the severity and incidence of this disease. Besides that, the data of cultivation technique and the condition of the garden were taken from the officer at those locations. Soil sample from each location was taken in a composite way, then its physical and chemical components were analyzed. The analysis was conducted to find out the correlation between cultivation and disease severity using chi-square test.  The relationship between chemical and physical factors of the soil with the disease severity was analyzed using a multivariate test of principal component analysis/PCA. Regression analysis was conducted to show the possible relation to the incidence and severity of this disease.  The location, clones, weed control and the number of plants per hectare showed a correlation with the disease severity. There was a positive correlation between incidence and severity of the disease. The highest disease severity occurred at the Sembawa location on clone BPM 24, with the number of plant population per ha was ? 555 trees and weed control using herbicide. Content of soil nitrogen, dust, clay and water as well as cation exchange capacity (CEC)were suggested to significantly contribute to the severity of stem canker.